Relationship Stressors with Stress and Student Learning Achievement (Coss Sectional Study at STIKES Nani Hasanuddin Makassar) - Rezki Yalatri Wirastuty (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
Physical environmental stressor, psychological, environmental stressor, and burden in learnings are representing the source stress student can reside at stress condition. Stress realized by the student would influence the learning process so it will affect learning achievement. This study was aimed to explain the relation of stressor student by stress and learn achievement in STIKES NaniHasanuddin Makassar. The design used in this study was the cross-sectional design. The sample consisted of 113 respondent, taken from the students of DIII Pharmacy STIKES NaniHasanuddin Makassar Semester III and V. Sample was taken using by purposive sampling. Data gathered were Analyzed by Spearman Rho Tests with significant level p < 0,05. Result showed that relation of student stressor with stress was ( p = 0,000 ) and relation of student stressor with learn achievement ( p = 0,000). This result was an indication that there was a relation between student stressor with stress and stressor student with learning achievement. It can be concluded that student stressor has a correlation with student stress and learn achievement. If student stressor accepted increasing so, student stress would increase, and progressively lower the stressor accepted it would increase learn achievement. Some things that can be done is the improvement of learning facilities and creating a conducive environment.